The relationship between inquiry-based teaching and students' achievement. New evidence from a longitudinal PISA study in England. (August 2022) - Jerrim, John; Oliver, Mary; Sims, Sam
Abstract: Inquiry-based science teaching involves supporting pupils to acquire scientific knowledge indirectly by conducting their own scientific experiments, rather than receiving scientific knowledge directly from teachers. This approach to instruction is widely used among science educators in many countries. However, researchers and policymakers have recently called the effectiveness of inquiry approaches into doubt. Using nationally-representative linked survey and administrative data we find little evidence that the frequency of inquiry-based instruction is positively associated with teenagers' performance in science examinations. This finding is robust to the use of different measures of inquiry, different measures of attainment, across classrooms with varying levels of disciplinary standards and across gender and prior attainment subgroups.